Efficacy of Recombinant Canine Distemper Virus Expressing Leishmania Antigen against Leishmania Challenge in Dogs. - Ryuichi Miura; Takanori Kooriyama; Misako Yoneda; Akiko Takenaka; Miho Doki; Yasuyuki Goto; Chizu Sanjoba; Yasuyuki Endo; Tomoko Fujiyuki; Akihiro Sugai; Kyoko Tsukiyama-Kohara; Yoshitsugu Matsumoto; et al. (Public Library of Science (PLoS), 2015)
Canine distemper virus (CDV) vaccination confers long-term protection against CDV reinfection. To investigate the utility of CDV as a polyvalent vaccine vector for Leishmania, we generated recombinant CDVs, based on an avirulent Yanaka strain, that expressed Leishmania antigens: LACK, TSA, or LmSTI1 (rCDV-LACK, rCDV-TSA, and rCDV-LmSTI1, respectively). Dogs immunized with rCDV-LACK were protected against challenge with lethal doses of virulent CDV, in the same way as the parental Yanaka strain. To evaluate the protective effects of the recombinant CDVs against cutaneous leishmaniasis in dogs, dogs were immunized with one recombinant CDV or a cocktail of three recombinant CDVs, before intradermal challenge (in the ears) with infective-stage promastigotes of Leishmania major. Unvaccinated dogs showed increased nodules with ulcer formation after 3 weeks, whereas dogs immunized with rCDV-LACK showed markedly smaller nodules without ulceration. Although the rCDV-TSA- and rCDV-LmSTI1-immunized dogs showed little protection against L. major, the cocktail of three recombinant CDVs more effectively suppressed the progression of nodule formation than immunization with rCDV-LACK alone. These results indicate that recombinant CDV is suitable for use as a polyvalent live attenuated vaccine for protection against both CDV and L. major infections in dogs.